Identification of the novel tigecycline resistance gene tet(X6) and its variants in Myroides, Acinetobacter and Proteus of food animal origin. (18th February 2020) - Liu, Dejun; Zhai, Weishuai; Song, Huangwei; Fu, Yulin; Schwarz, Stefan; He, Tao; Bai, Li; Wang, Yang; Walsh, Timothy R; Shen, Jianzhong
Abstract: Objectives: To report a novel tigecycline resistance gene, tet (X6), and its variants in four bacterial species isolated from chickens and pigs in China. Methods: WGS was conducted to identify the suspected resistance genes in the tigecycline-resistant Myroides phaeus 18QD1AZ29W. Functional cloning, homology modelling and molecular docking were performed to compare the function with other Tet(X) variants. Retrospective screening for tet (X6) was conducted for 80 isolates in our WGS data collection, and all genomic environments of tet (X6)-positive isolates were analysed. Results: The tigecycline-resistant M. phaeus 18QD1AZ29W isolated from a pig farm in Shandong in 2018 was positive for tet (X2) and a novel tet (X) gene, designated tet (X6). Tet(X6) could increase the MICs of all tested tetracyclines/glycylcyclines for Escherichia coli only 2- to 4-fold, which was possibly due to a lower tetracycline binding capacity of Tet(X6) compared with that of other Tet(X) variants. Retrospective screening showed that seven other isolates (7/80, 8.8%), comprising four Proteus spp. and three Acinetobacter spp. from chickens and pigs in Shandong and Guangdong, were positive for three different variants of tet (X6). The analysis of the genomic environment revealed that two tet (X6)-positive isolates from M. phaeus and Proteus cibarius, respectively, contained IS CR2, which may play a role in tet (X6) transmission. Conclusions: This study identified a novel type of tigecycline resistance gene, tet (X6), in Myroides, Acinetobacter and Proteus from chickens and swine. Tet(X6) conferred lower tetracycline/glycylcycline MICs than other Tet(X) variants, and IS CR2 may play a role in the transmission of tet (X6).